Corporate Social Responsibility and Business Performance in Takaful Agencies: The Moderating Role of Objective Environment - Nazri, Muhamad Azrin; Omar, Nor Asiah; Aman, Aini; Ayob, Abu Hanifah; Ramli, Nur Ainna (Mdpi, 2024)
Indexed by WOS/Scopus